2017
DOI: 10.1038/cddis.2017.451
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with A2A receptor antagonist KW6002 and caffeine intake regulate microglia reactivity and protect retina against transient ischemic damage

Abstract: Transient retinal ischemia is a major complication of retinal degenerative diseases and contributes to visual impairment and blindness. Evidences indicate that microglia-mediated neuroinflammation has a key role in the neurodegenerative process, prompting the hypothesis that the control of microglia reactivity may afford neuroprotection to the retina against the damage induced by ischemia–reperfusion (I–R). The available therapeutic strategies for retinal degenerative diseases have limited potential, but the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 51 publications
2
60
0
Order By: Relevance
“…Modeling ocular hypertension in vitro increased the expression of TSPO and MHC‐II in retinal neural cells, consistent with a response of microglia to elevated pressure. Also, A 2A R antagonist prevented this increase, suggesting that microglial A 2A R controls neuroinflammation, as has been suggested previously (Boia et al, ; Madeira et al, ).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Modeling ocular hypertension in vitro increased the expression of TSPO and MHC‐II in retinal neural cells, consistent with a response of microglia to elevated pressure. Also, A 2A R antagonist prevented this increase, suggesting that microglial A 2A R controls neuroinflammation, as has been suggested previously (Boia et al, ; Madeira et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…The blockade of A 2A R confers neuroprotection in several models of neurodegeneration, including in the retina (Boia et al, ; Boia et al, ; Cunha, ; Gomes, Kaster, Tome, Agostinho, & Cunha, ; Gyoneva et al, ; Liu et al, ; Madeira, Boia, et al, ; Madeira, Elvas, et al, ). One of the mechanisms that may explain the protective properties of A 2A R antagonists is the control of microglia‐mediated neuroinflammation (Cunha, ; Gomes et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of nonselective and selective A 2A R antagonists, such as caffeine and SCH 58261, respectively, is considered as a potential therapeutic strategy for several neuropathological diseases (Boia et al, ; Laurent et al, 2014). In line with these studies, we suggest that this neuroprotective effect observed might be associated to a direct effect on astrocytic transcriptome by particularly downregulating the pro‐inflammatory gene, Il1ß, as well as decreasing Vim expression.…”
Section: Discussionmentioning
confidence: 99%
“…The different types of astrocytic reactivation, Panreactive, A1 and A2 specific were classified in Zamanian et al (2012). A1-specific reactivation is highly associated with neurodegenerative diseases, such as AD [Color figure can be viewed at wileyonlinelibrary.com] suggested that A 2A Rs expressed by microglia, the main resident inflammatory brain cell, play a critical role in the control of neuroinflammation (Rebola et al, 2011;Boia et al, 2017). Some findings suggest that microglia A 2A Rs might also be dysregulated in the pathological context of AD (Orr et al, 2009;Angulo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%